Surprised by Hope : rethinking heaven, the resurrection, and the mission of the church - Wright, Tom. (London : SPCK, 2007)
Offers a reinterpretation of biblical teaching on what happens after death, arguing that literal bodily resurrection is at the heart of Christianity and exploring the implications of this for the church's work in the world.
All dressed up and no place to go? -- Puzzled about paradise? -- Early Christian hope in its historical setting -- The strange story of Easter -- Cosmic future : progress or despair? -- What the whole world's waiting for -- Jesus, heaven, and new creation -- When He appears -- Jesus the coming judge -- The redemption of our bodies -- Purgatory, paradise, hell -- Rethinking salvation : heaven, earth, and the Kingdom of God -- Building for the Kingdom -- Reshaping the church for mission : Biblical roots -- Reshaping the church for mission : living the future.
Includes Index.
Keywords: Eschatology; Resurrection; Mission of the church